Adrenocortical neoplasm with myxoid changes and pseudoglandular pattern: A case report and literature review - Zhang, Miao; Elsayes, Khaled; Guo, Charles C.; Hansel, Donna E. (Human Pathology Reports, 2025)
Adrenocortical neoplasms with myxoid change are very rare. Herein, we report a case of a 67-year-old man with a history of pancreatic adenocarcinoma status post distal pancreatectomy. During follow-up, PET/CT scan revealed a 2.8 cm tumor involving the left adrenal gland, which was resected. Microscopic examination showed a glandular-appearing lesion involving the adrenal cortex, which raised the differential diagnosis of metastatic pancreatic cancer. Initial immunohistochemical stains showed the lesional cells were negative for CK7, focally positive for pan cytokeratin, and retained SMAD4. Additional evaluation showed the tumor cells were diffusely positive for SF-1, Melan-A, CD56; focally positive for calretinin, and inhibin; and negative for CK20, CDX2, TTF-1, and chromogranin. A Ki67 index was 5 %. While these findings excluded pancreatic adenocarcinoma, they raised the differential diagnosis of adrenal cortical adenoma and/or carcinoma. Final diagnosis was myxoid adrenocortical tumor of uncertain malignant potential (MAT-UMP) following consensus review. In this case report and review, we highlight the diagnostic challenges of MAT-UMP, discuss potential pitfalls associated with this diagnosis, and review literature on this unusual entity.